2020
DOI: 10.1200/jco.19.02492
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Mutant IDH1 Inhibitor Ivosidenib: Safety and Clinical Activity in Patients With Advanced Chondrosarcoma

Abstract: PURPOSE Surgery is the primary therapy for localized chondrosarcoma; for locally advanced and/or metastatic disease, no known effective systemic therapy exists. Mutations in the isocitrate dehydrogenase 1/2 (IDH1/2) enzymes occur in up to 65% of chondrosarcomas, resulting in accumulation of the oncometabolite D-2-hydroxyglutarate (2-HG). Ivosidenib (AG-120) is a selective inhibitor of mutant IDH1 approved in the United States for specific cases of acute myeloid leukemia. We report outcomes of patients with adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 36 publications
3
71
0
Order By: Relevance
“…Additionally, studies have also shown that glutamate levels are lower in mutant IDH tumors compared to normal brain 61 . When assessing the effect of mutant IDH inhibitors in our cells, we observed that IDH1mut inhibition led to the expected decrease in steady-state 2-HG, in line with prior in vitro , in vivo , and ex vivo studies with AG-120 and AG-881 9 - 11 , 48 , 49 , 55 , 62 - 64 . Furthermore, and consistent with our hypothesis that the IDH1mut biomarkers would be reversed with treatment, we also observed a significant increase in steady-state glutamate in both NHAIDH1mut and U87IDH1mut cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Additionally, studies have also shown that glutamate levels are lower in mutant IDH tumors compared to normal brain 61 . When assessing the effect of mutant IDH inhibitors in our cells, we observed that IDH1mut inhibition led to the expected decrease in steady-state 2-HG, in line with prior in vitro , in vivo , and ex vivo studies with AG-120 and AG-881 9 - 11 , 48 , 49 , 55 , 62 - 64 . Furthermore, and consistent with our hypothesis that the IDH1mut biomarkers would be reversed with treatment, we also observed a significant increase in steady-state glutamate in both NHAIDH1mut and U87IDH1mut cells.…”
Section: Discussionsupporting
confidence: 85%
“…Clinical trials with AG-120 have shown substantial 2-HG reduction and disease control in patients with advanced tumors including acute myeloid leukemia (AML) and chondrosarcoma (e.g. clinicaltrials.gov NCT02073994 and NCT02074839) 11 , 55 , and AG-120 continues to be investigated either alone or in combination with traditional chemotherapies (e.g. clinicaltrials.gov NCT03245424 and NCT03173248).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with IDH (WT)/TET2 (WT) myeloid leukemia, a high level of BCAT1 is a strong predictor of worse survival outcomes, and the BCAT1 level significantly increases on disease relapse (Raffel et al, 2017 ). In recent years, IDH inhibitors targeting IDH mutants, including ivosidenib and enasidenib ( Table 1 ), have been approved by the Food and Drug Administration to be used in patients with IDH1 or IDH2 mutant recurrent or refractory AML, respectively (Kim, 2017 ; Dhillon, 2018 ), while trials of IDH inhibitors for other tumors such as cholangiocarcinoma, chondrosarcoma, and myelodysplastic syndrome are still underway (Abou-Alfa et al, 2020 ; Stein et al, 2020 ; Tap et al, 2020 ). Unlike α-KG, abnormal accumulation of succinate and fumarate in tumor tissues represses PHD, thus reducing HIF1 α hydrolysis, suppressing demethylation of DNA and histones, and promoting the occurrence and development of tumors (Cavalli and Heard, 2019 ).…”
Section: Amino Acid Metabolism and Epigeneticsmentioning
confidence: 99%
“…Mutations in IDH1 and IDH2 genes have been described in several malignancies, including gliomas [ 68 ], acute myeloid leukemia (AML) [ 69 , 70 ], and myelodysplastic disorders [ 71 ]. IDH1 / 2 mutations are also documented in cartilaginous neoplasms, including approximately 50% of patients with CHS (65% of conventional CHSs and up to 57% of dedifferentiated CHSs) [ 60 , 72 , 73 , 74 ]. However, these mutations were not found in the clear cell [ 37 ] and mesenchymal CHS [ 60 ].…”
Section: Genetics Of Chondrosarcomamentioning
confidence: 99%